Economic Survey of Latin America and the Caribbean 2020 - Economic Commission for Latin America; the Caribbean (United Nations, 2021)
This publication outlines the region’s economic performance in 2019 and analyses trends in the early months of 2020, as well as the outlook for the rest of the year. It examines the external and domestic factors that have influenced the region’s economic performance, analyses the characteristics of growth, prices and the labour market, and draws attention to some of the macroeconomic policy challenges of the prevailing external conditions, amid mounting uncertainty stemming mainly from political factors. It analyses the dynamics of investment and its determinants, with a view to identifying the different variables on which public policy can act to influence the trajectory of investment. This edition also analyses the effects and challenges of the coronavirus disease (COVID-19) pandemic for the region during 2020 and the outlook that is taking shape for the years to come.